Anaemia in pregnancy: a pilot study - Hyder, SM Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
Anaemia in pregnancy is a common health problem. According to the last national nutrition survey of Bangladesh ( 1981-1982), about 47% of the pregnant and lactating women had anaemia. Since then, a few community-based studies were done to investigate the anaemia prevalence. The present study aimed to investigate the anaemia prevalence in two rural locations of Bangladesh. The data were collect in March 1997 on 90 pregnant women from 6 villages of Saturia and another 6 vi11ages of Fulbaria Thana in Manikgonj and Mymensingh District respectively. All the identified pregnant women in the 12 villages who were willing to • participate were included in the study. The result shows that 54% of the women had anaemia according to the WHO definition. Area of residence, literacy, iron tablet intake and length of BRAC membership were significantly associated with a lower prevalence of anaemia (p<0.05). BRAC' s rural development and health programmes should find ways to increase coverage, compliance and effectiveness of its iron supplementation programme.